Traditional Food Glewo Rice As An Authentic Icon Of Semarang - Aletta Dewi Maria; Anas Harsanto (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Traditional or local food is one of the identifying characteristics of a community group that is easily found and recognized. Semarang City has a variety of culinary products from the cultural activities of its people. The diversity of cuisine reflects the personality and characteristics of the people of Semarang. Glewo rice cuisine is one of the things that must be preserved so that it does not disappear and is loved by all groups, especially the younger generation of culinary lovers. Many people do not know that Glewo rice has been a typical dish of old Semarang since the 1930s which is gradually losing its existence in today`s society. The purpose of this research is to increase the presence of Nasi Glewo which is almost forgotten, therefore it is necessary to have new innovations and creativity to revive the popularity of Glewo rice including using promotional media, collaboration, innovation, and festivals. The method used is descriptive qualitative by emphasizing the research process and the meaning of data and information. The results of this study show that Glewo Rice as a typical cuisine of Semarang city, has not entirely disappeared from the memory of the people of Semarang, still in order to be used as an authentic Semarang icon, it is necessary to collaborate with other parties, increase the promotion of Glewo rice and increase innovation in the presentation of Glewo rice. This can be by giving a touch of mixture with contemporary cuisine that is in great demand by the general public or served in places that are a favorite of the people of Semarang.